TEACHING ENGLISH LANGUAGE AT UNIVERSITY AS AN INSTRUMENT FOR PROMOTION OF SUSTAINABLE DEVELOPMENT THROUGH SOCIETY - Мелешко, Инна; Куценок, Неонила; Ямшинская, Наталия (SWorldJournal, 2021)
The authors of the article focus attention on the urgency of ecological problems the world faces today and consider sustainable development as a concept aimed to help save our planet for future generations. The paper addresses the great importance of qual